COMPARISON OF ANTEGONIAL INDEX MEASUREMENTS IN MALES AND FEMALES USING PANORAMIC RADIOGRAPHY WITH THE SMARTIMU APPLICATION - Muliani Ramli, Muliani Ramli; Pertiwisari, Amanah; Selviani, Yusrini; Jayadi Abdi, Muhammad; Husein, Husnah (YARSI Dental Journal, 2025)
Introduction: Bones are the primary structural components of the human body that have the ability to grow and develop. Loss of bone mass increases the risk of bone health disorders such as osteopenia and osteoporosis. One method for diagnosing osteoporosis is through panoramic radiography using radiometric measurements such as the Antegonial Index (AI). The measurement of the Antegonial Index can be conducted using the SmarTimu application. Objective: This study aimed to compare the Antegonial Index values between males and females. Methods: This research employed a cross-sectional design with purposive sampling, using panoramic radiographs from RSIGMP Universitas Muslim Indonesia that meet the inclusion criteria. Results: The right-side Antegonial Index in males was found to be 2.973, while the left-side index was 2.964. In females, the right-side Antegonial Index was 3.300, and the left-side index was 3.264. Conclusion: There is no significant difference in the Antegonial Index values between males and females based on panoramic radiography.